2011
DOI: 10.1007/s12199-010-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between environmental exposure to cadmium and bone metabolism in a non-polluted area of Japan

Abstract: The results of the present study suggest the possibility of bone metabolic disorder induced by environmental low-grade cadmium exposure. With respect to osteoporosis, a long-term follow-up survey is required to assess the tolerable intake of cadmium in environmental exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 35 publications
1
2
0
2
Order By: Relevance
“…Studies from other laboratories found that chronic Cd exposure (3 months) resulted in a concentration of 4 mg/L in the blood of the mice (36). This concentration was slightly higher than the general population, but significantly lower than humans with occupational exposures (37)(38)(39)(40)(41). Taken together, these data show that the dose of Cd used in this study is environmentally relevant and comparable to that of human exposures.…”
Section: Micesupporting
confidence: 47%
“…Studies from other laboratories found that chronic Cd exposure (3 months) resulted in a concentration of 4 mg/L in the blood of the mice (36). This concentration was slightly higher than the general population, but significantly lower than humans with occupational exposures (37)(38)(39)(40)(41). Taken together, these data show that the dose of Cd used in this study is environmentally relevant and comparable to that of human exposures.…”
Section: Micesupporting
confidence: 47%
“…An earlier report showed that mean serum level was 0.46 μg/L among non-smoking women 35 . A report from Japan found that mean serum Cd level was 1.57 μg/L among women from a non-polluted area 36 . According to a small case-control study, maternal serum Cd level during pregnancy was 2.22 μg/L among subjects delivered with babies with normal birth weight and 3.33 μg/L among subjects delivered with babies with low birth weight 37 .…”
Section: Discussionmentioning
confidence: 99%
“…U-cd concentration was 2.29 μg/g creatinine in the study, this was less than biologic exposure indices (BEI), 5 μg/g creatinine. Moreover, in the Korean lead worker study, urine cadmium concentration was 0.98 μg/g creatinine [ 17 ], while 1.93 μg/g creatinine was evident in a Japenese population study [ 18 ]. We found that B-cd level and U-cd level of residents in abandoned mines was relatively higher than other population.…”
Section: Discussionmentioning
confidence: 99%